2005
DOI: 10.1136/adc.2004.067272
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relation between limited joint mobility, height, insulin-like growth factor 1 levels, and risk of developing microalbuminuria: the Oxford Regional Prospective Study

Abstract: Aims: To determine risk factors for development of microalbuminuria (MA) in relation to detection of limited joint mobility (LJM+) of the interphalangeal joints in a longitudinal cohort of type 1 diabetic (T1DM) subjects. Methods: A total of 479 T1DM subjects diagnosed ,16 years were followed from diagnosis of diabetes with annual assessments consisting of assessment of LJM, measurement of HbA1 c and insulin-like growth factor 1 (IGF-1), and three urine samples for albumin:creatinine ratio (ACR). Results: Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…Those with mild LJM had four times the excess below the 25th percentile (72%), with no important difference for those with moderate to severe limitation (77% below the 25th percentile) (12). The Oxford study also found an association of LJM with growth limitation (13).…”
Section: Effects On Growthmentioning
confidence: 52%
See 1 more Smart Citation
“…Those with mild LJM had four times the excess below the 25th percentile (72%), with no important difference for those with moderate to severe limitation (77% below the 25th percentile) (12). The Oxford study also found an association of LJM with growth limitation (13).…”
Section: Effects On Growthmentioning
confidence: 52%
“…Although cross-sectional studies suggested that duration of diabetes was the most important variable in the appearance of LJM, when the time of development of joint changes could be determined, attained age was of greater importance (12), an observation confirmed later by the large longitudinal Oxford Regional Prospective Study (13). The progression from detection of mild limitation to moderate or severe changes varied from 3 months to 4 years, with a mean of 2 years.…”
Section: Natural Historymentioning
confidence: 79%
“…The Diabetes Control and Complications Trial showed that intensive glycaemic control in adolescents with type 1 diabetes mellitus is associated with a decreased risk of microvascular complications [1], and there is increasing evidence that control of diabetes during the prepubertal and pubertal years can also have a marked impact on the risk of such complications [2,3]. As a result, current guidelines recommend that the aim of treatment in children and adolescents with type 1 diabetes should be to achieve nearnormal glycaemic control as early as possible in the course of the disease [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A study on type 2 diabetes progression suggests that TCF7L2 may be associated with insulin secretion [6]. [7]) and 7,596 geographically matched White control subjects (from the 1958 British Birth Cohort [8]) using TaqMan® 5′ nuclease assay (Applied Biosystems, Warrington, UK). All type 1 diabetic subjects were diagnosed under the age of 17 years.…”
mentioning
confidence: 99%